Program Pengenalan Jurusan Teknik Melalui Aktivitas Fun Science Experiment Bagi Siswa MTS Darul Hikmah - RYANU, HARFAN HIAN; Pramudita, Aloysius Adya; Sudjai, Miftadi (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Madrasah Tsanawiyah (MTS) is a formal education provider at the junior high school level with more emphasis on the content of Islamic Religious Education. MTS students generally have low exposure to the world of science and engineering so that very few/rare madrasah students continue their education, especially lectures in Engineering majors. This community service activity with the title